Epidemiological analysis of AIDS/HIV case notifications in Brazilian Goiás State from 2012 to 2022 (Research, Society and Development, 2024)
Acquired Immunodeficiency Syndrome (AIDS) is caused by HIV, an RNA retrovirus that targets CD4 T lymphocytes of the immune system. HIV infection, transmitted through sexual contact, blood exposure, or mother-to-child transmission, progresses in stages and can lead to severe immunodeficiency and vulnerability to opportunistic infections. This study aims to analyze the epidemiological profile of AIDS/HIV patients reported in the SINAN-DATASUS system between 2012 and 2022 in the state of Goiás. Regarding the methodology, this is a cross-sectional, quantitative, observational, and descriptive study based on secondary data. The variables analyzed include age group, source of infection, education level, race, and sex, and a chronological analysis to evaluate the absolute frequency of cases over the 10 years studied. Data were transcribed into Excel® and analyzed using BIOESTAT software, applying absolute and relative frequency, mean, and percentage variation calculations. HIV infection predominantly affects men aged 20–34 years, self-identified as mixed race, with low educational levels, and who primarily contracted the virus through heterosexual relations. The study revealed significant trends in the spread of HIV/AIDS in Goiás, characterizing its epidemiological profile. Thus, it underscores the need for targeted prevention and public health education efforts, particularly for more vulnerable groups, to control the epidemic in Goiás State.